2017
DOI: 10.5539/jgg.v9n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Subsurface Evidence for Postglacial Holocene Lakes at Ivanpah Dry Lake: An Alternative Energy Development Site in the Central Mojave Desert, California, USA

Abstract: Dry lakes, or playas, in the American Southwest have become important locations for alternative energy solar electric generation systems. Many of these playas have not been investigated for past environmental conditions prior to their development, causing alterations to the shallow sediment profile and altering subsurface chemical and physical data important to recent geologic and hydrologic histories of these areas. Recent studies of these features commonly have focused on surficial data with little or no sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Case examples 3 and 4 uses data collected mainly by the author and a few water isotope samples from Newton and Allen [24]. Case example 2 uses raw data collected by Waring and Sims and Spaulding and reinterpreted in relation to modern flow capacity [25,26]. Case examples 1 and 5 uses information developed in studies by Miner et al, Duffy and Al Hassan [27], and Hamann et al [13,17,28].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Case examples 3 and 4 uses data collected mainly by the author and a few water isotope samples from Newton and Allen [24]. Case example 2 uses raw data collected by Waring and Sims and Spaulding and reinterpreted in relation to modern flow capacity [25,26]. Case examples 1 and 5 uses information developed in studies by Miner et al, Duffy and Al Hassan [27], and Hamann et al [13,17,28].…”
Section: Methodsmentioning
confidence: 99%
“…Sims and Spaulding reported that transitional lakes existed in Ivanpah Valley in two Holocene and one Pleistocene-Holocene transitional period [26]. The deepest and longest was a lake unit that was dated at a high stand at ca.…”
Section: Case Example 2-paleoclimate and Salinity Of Ivanpah Valley Usamentioning
confidence: 99%
See 3 more Smart Citations